2016
DOI: 10.1016/j.trim.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

High expression of heme oxygenase-1 in target organs may attenuate acute graft-versus-host disease through regulation of immune balance of TH17/Treg

Abstract: The high incidence of acute graft-versus-host disease (aGVHD) is a serious complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Grades III and IV aGVHD are the leading causes of death in allo-HSCT recipients. Heme oxygenase-1(HO-1) has anti-inflammatory and immune-regulatory functions. In this study, we evaluated the none GVHD and grade I-IV patients samples which were collected at the first re-examination after successful allo-HSCT, we found that expressions of HO-1 mRNA in the bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…It has been proposed that a higher HO-1 expression level prevents the progression of GVHD and acts prophylactically on sinusoid obstruction syndrome (SOS), while promoting relapse [39][40][41]. Although the results of this study suggest that the higher expression of HO-1 is associated with favorable survival outcomes after allo-HSCT, the higher expression of HO-1 has not been shown to affect the risk of disease relapse or the development of GVHD.…”
Section: Discussioncontrasting
confidence: 57%
“…It has been proposed that a higher HO-1 expression level prevents the progression of GVHD and acts prophylactically on sinusoid obstruction syndrome (SOS), while promoting relapse [39][40][41]. Although the results of this study suggest that the higher expression of HO-1 is associated with favorable survival outcomes after allo-HSCT, the higher expression of HO-1 has not been shown to affect the risk of disease relapse or the development of GVHD.…”
Section: Discussioncontrasting
confidence: 57%
“…Given that both the amount and the function of Tregs were inhibited in vitiligo, we speculated that restoring Treg function may also be effective in treating vitiligo. Previous studies have concluded that HO‐1 expression is necessary for Tregs to exert their immunoregulatory function . Up‐regulation of HO‐1 activity in vivo can inhibit several immune response, including the proliferation of lymphocytes and cytotoxic immune cells‐mediated cytotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…GvHD is commonly observed after hematopoietic stem cell transplants, when T cells present in the graft attack the tissues of the transplanted recipient. After perceiving host tissue antigens, among them the human leukocyte antigens, as antigenically foreign, T cells produce an excess of cytokines, including tumor necrosis factor alpha (TNFα) and interferon gamma (IFNγ) ( 25 , 27 , 71 ).…”
Section: Innate Immunity As a Potential Trigger Of Gvhdmentioning
confidence: 99%
“…On the other hand, chronic activation of the MBL pathway is most likely an important element in BM aging and myelodysplasia ( 20 23 ). This pathway also likely contributes based on some clinical observations to induction of graft-versus-host disease (GvHD) after histoincompatible hematopoietic transplantation ( 24 27 ).…”
Section: Introductionmentioning
confidence: 99%